Haematological and serum biochemical changes in pigs administered with ascorbic acid and transported by road for four hours during the harmattan season - A.Y. Adenkola; J.O. Ayo; A.K.B. Sackey; A. B. Adelaiye (African Journal of Pig Farming, 2016)
This study was conducted with the aim of investigating the effect of ascorbic acid (AA) on haematology and serum biochemical responses of pigs transported for short journey (4 h) during the harmattan season. Sixteen pigs administered with AA at a dose of 250 mg/kg per os and individually served as experimental animals, and 13 others each administered orally with sterile water served as control animals. The animals were then transported for 4-h at a speed of 40- 50 km/h covering a distance of 140 km. Blood samples were taken early in the morning a day before transportation, immediately after and a week after transportation. The leucocyte count (15830.25 ± 1063.08 × 103 /µl) dropped (P < 0.05) in the experimental pigs after transportation and the value was significantly (P < 0.05) lower than the value of 22010.69 ± 1722.00 × 103 /µl obtained in the control pigs after the journey. The neutrophils: lymphocyte ratio obtained in the control animals increased from 0.61 ± 0.04 before transportation to 0.79 ± 0.17 immediately after transportation. There was a significant (P < 0.05) increase in total protein post– transportation in all experimental and control groups, but the increase was higher in the control than the experimental group. Alkaline phosphatase and aspartate amino transferase values in the control pigs increased immediately after transportation. This study indicates for the first time the beneficial effect of AA administration on haematology of pigs transported by road during the harmattan season for short journey of 4 h. It is, therefore, recommended that pigs be administered with AA before transportation by road during the harmattan season in order to reduce the risk of adverse effects of transportation stress on health.